Wattpad Apps to Increase Indonesian Youth’s Interest in Reading and Writing - Lestari, Puji Ayu; Hasanudin, Cahyo (Proceedings International Conference on Education Innovation and Social Science, 2022)
The younger generation is a generation that has a responsibility to carry on the nation's ideals, always wants to try new things, and has a variety of hobbies for the future. In preparing for the future, we can start by increasing interest in reading and writing. This study aims to determine the role of the Wattpad application in increasing interest in reading and writing interest in the younger generation of Indonesia. This research is a literature study, researchers need to find and use data sources or previous research in the form of scientific journals, articles, and books related to the research topic. Researchers use the theory of Mary W. George. In data validation, researchers used data triangulation techniques. Wattpad is an application or site that facilitates users in doing writing and reading activities. Before using the Wattpad application, we need to create a Wattpad account first. You can create a Wattpad account using your email address or Facebook account. After creating an account, we can read various stories on Wattpad and can publish literary works.